Incidence of "notified" cases of domestic violence against children and adolescents during the covid-19 pandemic in the demographic region of southwestern Paraná - Massagli, Silvia Carla Conceição; Silva, Gabrielle Klein; Da Silva , Isadora Klein; e Silva , Sandy Ianka Lima (Seven Editora, 2023)
The objective of this study is to map the evidence found in the Database of the National Information System for Childhood and Adolescence (SIPIA) of the Tutelary Council of the mesoregion of Southwest Paraná in 42 cities that make up the geography of Domestic Violence against Children and Adolescents (VDCA). This breakdown is by region and pre-pandemic, pandemic, and post-pandemic period and demonstrates the impacts of the COVID-19 pandemic on VDCA. About the methodology adopted, this is documentary research of the quantitative-qualitative type. The results brought a "surprise" and proved to be quite frightening with the number of municipalities that do not feed in SIPIA the notifications of cases of VDCA, zeroing out all the years surveyed. There are 15 municipalities: Clevelândia, Honório Serpa, Coronel Domingos Soares, Renascença, Salgado Filho, São João, Salto do Lontra, Saudade do Iguaçu, Santo Antônio do Sudoeste, Realeza, Santa Izabel do Oeste, Cruzeiro do Iguaçu, Barracão, Verê and Francisco Beltrão. Still in this analysis about the "disregard" with the information, we have Pato Branco, Vitorino, Ampére, Pranchita and Marmeleiro with only one notification. Mariópolis and Manfrinópolis with two notifications and Coronel Vivida, Itapejara d’Oeste, Sulina, Enéas Marques and São Jorge d’Oeste with only three notifications in 6 years of research. The data explored by the SIPIA system referred to 6 years of notifications (2018-2023). In the case of the pandemic period, 2020 and 2021, only 40 cases were reported in the mesoregion of Southwest Paraná compared to the previous year (2019) in which 162 cases of VDCA were reported. Among the typologies of cases, we have in 1st place Physical Violence, with 21 notified cases. In 2nd, Sexual Violence with 17 cases. In 3rd, Psychological Violence with 9 cases. In the Sexual Exploitation typology, there are no notifications to be commented on. The data reported from the pandemic period (2020-2021) made it possible to outline. There is a "perverse ranking", in which the hidden figure of the researched data and the fact of the underreporting of cases of VDCA prevent the construction of knowledge about the theme studied. The construction of knowledge takes place in a historical process that cannot do without criticism, debate, and the confrontation of data. The absence of this debate due to the lack of information on the incidence of cases weakens criticism and scientific thinking and limits intervention in the fight against VDCA. Taking into account factors such as fear of contamination, imposed social isolation, limitations on distancing from home, and financial difficulties arising from the pandemic – factors that could aggravate VDCA – these underreporting generate perplexity. At the same time, these factors may have caused obstacles to the reporting of VDCA and to the search for assistance and the consequent decrease in notifications. Therefore, the limitations of this study are the high number of underreporting in the data provided by the municipalities of the Mesoregion of Southwest Paraná regarding the VDCA through SIPIA. DOI:https://doi.org/10.56238/emerrelcovid19-060